Tissue ischemia due to CO2 pressure during laparoscopic radical prostatectomy - Vodopija, Nado (Array, 2009)
Abstract: Laparoscopic radical prostatectomy is nowadays one of the most frequently performed urological surgical procedures. For insufflation in laparoscopic radical prostatectomy (LRP) CO2 is used, with the pressure in the operative region between 12 and 15 mm Hg. At the microcirculation level, the pressure is lower, which raises the possibility of ischemic tissue damage during the procedure. The activity of glutathione peroxidase (GSH-px), superoxide dismutase (SOD) and catalase (CAT) was measured at the beginning and immediately after the end of the surgery in 44 patients who underwent LRP and in 11 who underwent retropubic radical prostatectomy (RRP). Capillary endothelial damage was assessed by applying immunohistochemical and morphometric methods to tissue samples from the urinary bladder neck, which contains all layers of the bladder wall. Measurement of the enzyme activity showed no significant increase of GSH-px (p-0.431), SOD (p-0.220) and CAT (p-0.434) levels. Neither immunohistochemical analysis of the bladder neck capillaries with i-nitric oxide synthase (i-NOS) nor morphometric analysis showed signs of endothelial ischemic damage